ANALISIS PENGARUH INVESTMENT OPPORTUNITY SET, FREE CASH FLOW DAN TOTAL ASSET TURNOVER TERHADAP KEBIJAKAN DIVIDEN (STUDI EMPIRIS PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014) - admin, Rendy Agus Pratama B11112066 (Jurnal Manajemen Update, 2016)
The purpose of this research was to find empirical evidence of the influence investment opportunity set, free cash flow and total asset turnover towards dividend policy. This study uses the LQ45 company listed in Indonesia Stock Exchange period 2010-2014. The sampling technique used is purposive sampling. The final sample size used is 74 samples. Techniques data analysis was using multiple linear regression. The results of F test showed the regression model that built has accomplished goodness of fit model test. Results of t test showed that investment opportunity set and free cash flow have a significant positive effect on dividend policy (Dividend payout Ratio). The positive effect of investment opportunity set was not as expected where the proposed hypothesis is the existence of a negative influence. Total asset turnover has no effect on dividend policy. Keywords: Investment Opportunity Set, Free Cash Flow, Total Asset Turnover and Dividend Policy